12th International Symposium on Haptic Interfaces for Virtual Environment and Teleoperator Systems, 2004. HAPTICS '04. Proceedi 2004
DOI: 10.1109/haptic.2004.1287227
|View full text |Cite
|
Sign up to set email alerts
|

Vibrotactile letter reading using a low-resolution tactor array

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 16 publications
1
50
1
Order By: Relevance
“…It is difficult to compare accuracy performance using the VHD with other devices since previous studies examining recognition of complex stimuli did not employ an active scanning method (see, e.g., Saida et al, 1982;Yanagida et al, 2004). However, when complex characters such as Japanese letters were presented sequentially (i.e., as if being written on the participant) accuracy performance was reported to be between 87% and 95% (in the Yanagida et al and Saida et al studies, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…It is difficult to compare accuracy performance using the VHD with other devices since previous studies examining recognition of complex stimuli did not employ an active scanning method (see, e.g., Saida et al, 1982;Yanagida et al, 2004). However, when complex characters such as Japanese letters were presented sequentially (i.e., as if being written on the participant) accuracy performance was reported to be between 87% and 95% (in the Yanagida et al and Saida et al studies, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…In our own work, we have looked at determining the limits of perception of the human back in terms of vibration intensity and location discrimination [11], as a means for directing the user's gaze for predominantly visual search tasks [12], and as a way of conveying information by way of strokes for writing letters [22].…”
Section: Tactile Cuing For Spatial Awarenessmentioning
confidence: 99%
“…By stimulating tactors in sequence, it is possible to create recognizable percepts with forms as complex as alphanumeric characters, and indeed, research has shown this to be the most effective way to present such a stimulus set [24]. However, this work has largely focused on relatively sparse arrays, often relying on subjects constructing a representation of the shapes being displayed through simple repeated stimuli localization.…”
Section: 2mentioning
confidence: 99%
“…Tan suggests that this could be used to point out potential dangers on the road to drivers, or highlight important onscreen information for workers in safety critical environments such as air traffic control. Work has also focused on human abilities to recognize spatiotemporal patterns, either relying on the well-studied task of letter recognition [24], or using a customized set of stimulus patterns [16]. Research examining how information can be encoded in single vibrating elements has also developed apace.…”
Section: Introductionmentioning
confidence: 99%